Strategi Guru Dalam Meningkatkan Perkembangan Sosial Anak Usia 5-6 Tahun Di Tk PGRI Dahlia Lombok - Bintang Shafa Masnaini. Z; Nisa Ali; Shafira Ramdhani; Uswatun Hasanah (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2022)
The purpose of this study was to determine the learning process, social development, teacher strategies in overcoming the problems of social development of children aged 5-6 years. This study uses a descriptive method and a qualitative approach. The data obtained in the form of words and pictures. The data sources consist of 2 teachers and 2 children in different classes. From the results of the study, it was found that in the learning process children aged 5-6 years with social development barriers were equated with children's learning in general, only adjustments were made in the use of learning tools and resources, materials and assessment of the child's condition. In the process of social development, children aged 5-6 years with social barriers tend to be selfish in playing and behaving, being less good at communicating, and causing more problems. The teacher's strategy in overcoming the problem of social development is that the teacher first overcomes it by being soothed with a loving hug, then the child is invited to talk calmly, and is helped to get to know the environment better.